Circulating inflammation markers and colorectal adenoma risk. (7th February 2019) - Huang, Wen-Yi; Berndt, Sonja I; Shiels, Meredith S; Katki, Hormuzd A; Chaturvedi, Anil K; Wentzensen, Nicolas; Trabert, Britton; Kemp, Troy J; Pinto, Ligia A; Hildesheim, Allan; Rothman, Nathaniel; Purdue, Mark P
Abstract: Inflammation is a driver of colorectal neoplasia; however, what particular inflammatory processes play a role in early carcinogenesis are unclear. We compared serum levels of 78 inflammation markers between 171 pathologically confirmed colorectal adenoma cases (including 48 incident cases) and 344 controls within the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial. We used weighted multivariable logistic regression to compute odds ratio (OR) and 95% confidence interval (CI). We found 14 markers associated with risk of adenoma overall; three of these were also associated with incident adenoma: CC-chemokine cysteine motif chemokine ligand 20 (CCL20) [overall adenoma fourth versus first quartile: OR 4.8, 95% CI 2.0–12, P trend 0.0007; incident adenoma third versus first tertile: OR 4.6, 95% CI 1.0–22, P trend 0.03], growth-related gene oncogene products (GRO) [OR 3.8, 95% CI 1.6–9.3, P trend 0.006 and OR 3.6, 95% CI 1.1–12, P trend 0.04, respectively] and insulin [OR 2.9, 95% CI 0.8–10, P trend 0.05 and OR 7.8, 95% CI 1.3–46, P trend 0.03, respectively]. All statistical tests were two-sided. These results provide important new evidence implicating CCL20- and GRO-related pathways in early colorectal carcinogenesis and further support a role for insulin. Abstract : While insulin has long been implicated in colorectal tumorigenesis, our results provide important new evidence, supported by clinical and experimental findings, implicating a role for CCL20- and GRO-related pathways in early colorectal carcinogenesis.